The eﬀect of internal migration on regional growth in Italy: a dynamic spatial panel data analysis - Francesca Centofanti; Roberto Basile; Francesca Licari; Jacopo Pitari (Investigaciones Regionales - Journal of Regional Research)
This study assesses the eﬀect of internal migration on regional growth in Italy at the NUTS-3 level over the period 2002-2019. The composition of the internal migration ﬂows of the working-age population in Italy during the sample period appears substantially heterogeneous in nationality and labor skills. The analysis considers this heterogeneity, estimating various speciﬁcations of the dynamic spatial model and controlling for the endogeneity of migration variables through a control function approach. e evidence suggests that the internal migration of Italian citizens has a positive direct and spillover impact on regional growth, slowing down the convergence process. On the contrary, there is no evidence of a signiﬁcant eﬀect of internal migration of foreign citizens. Taking the skill composition of internal movements of Italian citizens into account, the adverse impact on convergence is magniﬁed, thus corroborating the skill-selective hypothesis. Finally, the diverging impact of internal migration increases with the distance of migration ﬂows.